2011
DOI: 10.1152/ajpendo.00022.2011
|View full text |Cite
|
Sign up to set email alerts
|

Insulin regulates menin expression, cytoplasmic localization, and interaction with FOXO1

Abstract: Menin is the ubiquitously expressed nuclear protein product of the MEN1 gene, which interacts with PKB/Akt in the cytoplasm to inhibit its activity. This study describes a novel insulin-dependent mechanism of menin regulation and interaction with other metabolic proteins. We show that insulin downregulated menin in a time-dependent manner via the human insulin receptor. Inhibition analysis indicated a critical role for the protein kinase Akt in regulation of menin expression and localization. Insulin-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…A recent report described insulin-mediated down-regulation of menin and localization in the cytoplasm in a time-dependent manner via the human insulin receptor (55). It is conceivable that activation of the insulin signaling pathway by insulin leads to reduction in menin levels particularly in the nucleus, consequently resulting in decreased processing of pri-let-7a and increased Irs2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…A recent report described insulin-mediated down-regulation of menin and localization in the cytoplasm in a time-dependent manner via the human insulin receptor (55). It is conceivable that activation of the insulin signaling pathway by insulin leads to reduction in menin levels particularly in the nucleus, consequently resulting in decreased processing of pri-let-7a and increased Irs2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Menin binds to cytoskeletal proteins, e.g. vimentin [108], and cytoplasmic cell signalling mediators including Akt1/protein kinase B (PKB) and forkhead box protein O1 (FoxO1) [109, 110]. Some of the known menin interaction partners are depicted in Fig.…”
Section: Molecular Geneticsmentioning
confidence: 99%
“…Therefore, our study suggests that Menin could act as a novel co-repressor of LXRa in the liver. Interestingly, recent studies also found that Menin could interact with FOXO1, in response to insulin signaling [13]. Liver-specific hemizygous deletion of menin led to increased expression of FOXO1 target genes, such as IGFBP-1, PGC-1a, insulin receptor, and G6Pase [13].…”
Section: Discussionmentioning
confidence: 99%